Effect of paclobutrazol (PP333) on twig dieback of Myrica rubra and control - Chen Fangyong; Ni Haizhi; Wang Yin; Ren Zhengchu; Liu Jihong; Wang Yiguang (浙江大学学报. 农业与生命科学版)
Red bayberry (Myrica rubra (Lour.) Zucc) is one of the major fruits planted in Zhejiang Province, China. It provides an important financial support for the farmers in this area. However, the fungal disease twig dieback severely threats the growth of red bayberry. Once one plant is infected by this disease, it would spread and destroy the whole orchard in three years. Controlling technology on this disease is urgently needed at this area. Paclobutrazol (PP333) is a chemical widely used for plant growth regulation. It causes plant growth shorter, stronger, more branches and better fruiting. It has been widely used on the red bayberry for higher production. However, over-dosage use of the chemical PP333 is suspected to connect with the epidemic of twig dieback in Zhejiang, China. The causal agent of the twig dieback disease was proved to be Pestalotiopsis species. It is postulated that the application of PP333 inhibits some bacteria growth and breaks microbial community balance in the soil, so that the causal agent of twig dieback is predominant.In order to test the hypothesis, we investigated the correlation between application amount of PP333 and disease severity in eight farms in Zhejiang in four years. In the eight farms, we investigated the connection of application dosage of PP333 with the residues of the chemical in leaves, roots and fruits respectively. In different treatments of PP333, leaf colour, root architecture and fruit quality were also investigated. Application of three concentrations of PP333, T1(200 mg/kg), T2(300 mg/kg) and T3(500 mg/kg), resulted in light, moderate and heavy twig dieback disease, respectively. The results showed that over-dosage application of PP333 in successive years caused fruit tree early senility and server diseases infection.In order to cure the infected fruit trees, we applied a new home-made chemical to the infected trees. The results showed that the home-made chemical is quite effective to control the disease. After three years of treatment on the light infected orchard, all the disease infected trees were recovered to be healthy. However, the control orchard without treatment was more seriously infected. The infected trees occupied 74.7% and 21.6% trees died. In the moderate infected orchard, three years of treatment recovered over 90% of infected trees. The untreated control trees get infected to be 100%. In the heavy infected orchard, three years of treatment recovered over 50% of infected trees. As the control, all the untreated trees died in the fourth year. The results showed that the new home-made chemical was very effective to cure the infected trees.Physiological effects of PP333 on Dongkui red bayberry were also investigated. The higher concentration of PP333 (500 mg/kg) caused higher stomatal density and smaller stomatal size. Twig dieback severity was correlated with the amount of PP333 chemical residues in leaves and roots. Application of different amounts of PP333 to the trees had significant different residues of PP333 in leaves and roots. On the light, moderate and heavy infected fruit trees, the content of PP333 in leaves was 13.20, 25.60 and 439.00 μg/kg respectively and the content of PP333 in roots was 1.20, 3.38 and 266.00 μg/kg respectively, but the chemical residuals in fruits were very low.We concluded that over-dosage application of PP333 is the major cause of twig dieback disease predominance on red bayberry. The over-dosage application of PP333 promotes fruit tree early senility, then promotes Pestalotiopsis species infection, then causes twig dieback symptoms and tree dies, and then more Pestalotiopsis species are spread and more trees are infected. It forms a vicious cycle. To control the disease, our patented home-made chemical is effective.